2019
DOI: 10.3122/jabfm.2019.02.180259
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Diabetes Screening and Prediabetes Treatment during Office Visits in the US

Abstract: Introduction: The American Diabetes Association recommends annual screenings for prediabetes if the patient meets the suggested requirements. The overall prevalence of prediabetes has decreased from an estimated 86 million adults in 2012 to 84.1 million adults in 2015 in the United States. Along with lifestyle modifications, the use of metformin as a treatment option or in combination has shown a decrease in weight and health care costs. This study was designed to review the prevalence of screening and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
1
19
1
3
Order By: Relevance
“…In prior studies, health insurance, specifically private insurance coverage, 5 , 6 was associated with diabetes screening, but this was not seen in our study as the rate of screening was not significantly different for patients without insurance. Interestingly, we did find an increased rate of screening for patients with Medicare or Medicaid.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…In prior studies, health insurance, specifically private insurance coverage, 5 , 6 was associated with diabetes screening, but this was not seen in our study as the rate of screening was not significantly different for patients without insurance. Interestingly, we did find an increased rate of screening for patients with Medicare or Medicaid.…”
Section: Discussioncontrasting
confidence: 92%
“… 4 Studies have consistently found higher rates of screening in patients with female sex, older age, higher body mass index, non-white race, comorbidities such as hypertension or dyslipidemia, and regular medical health care. 4 - 6 One study on the impact of insurance showed that insured patients were more likely to receive screening. 5 Another study found that patients with private insurance were more likely to receive screening compared to patients with public insurance who were less likely to receive screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open access adoption of implementing pre-diabetes treatment guidelines in clinical practice is lacking. [9][10][11][12] When comparing those who know they have pre-diabetes to those with normal fasting serum glucose, those with pre-diabetes were more likely to report positive behavioural change such as weight control, increased exercise and fat and caloric reduction. 13 Yet less than 25% of patients with prediabetes reported having received lifestyle change advice during an office visit with their medical providers.…”
Section: Meaningmentioning
confidence: 99%
“…Recent data demonstrate that the incidence and prevalence of prediabetes is rising among US non-Hispanic Blacks and Hispanics. 1,2 While not all patients with prediabetes will develop type 2 diabetes, diabetes prevalence is projected to increase almost threefold by 2060, with non-Hispanic Black women having the highest rates of increase. 3 Rates of diabetes related complications, including major amputations, are also higher among Hispanic and non-Hispanic Black patients as compared to White patients.…”
Section: Introductionmentioning
confidence: 99%